Kentucky's Response to the Lautenberg Act: Curbing Domestic Violence Among Police - Kappeler, Victor E (1999)
This study empirically investigates the impact of the Lautenberg Act on policing in Kentucky to determine whether a significant proportion of law enforcement agencies have been affected by the law and to ascertain whether a significant percentage of Kentucky officers will be forced to find alternative employment